Application of magnetic Cd2+ ion-imprinted mesoporous organosilica nanocomposites for mineral wastewater treatment. Issue 13 (23rd January 2017) - Cen, Shuibin; Li, Weiming; Xu, Shiying; Wang, Zhihong; Tang, Youwen; Wang, Haishui; Wei, Chaohai
Abstract : This work demonstrates a simple strategy for producing highly selective adsorption magnetic ion imprinted mesoporous silica (MIIMS) nanocomposites. Abstract : This work demonstrates a simple strategy for producing highly selective adsorption magnetic ion imprinted mesoporous silica (MIIMS) nanocomposites. They have been functionalized by a γ-(aminoethylamino)propyl chelating group for specific recognition and rapid removal of toxic heavy metal ions from wastewaters. The superparamagnetic Fe3 O4 nanocrystal was encapsulated in an imprinted mesoporous organosilica shell via a co-condensation synthesis method. The results of transmission electron microscopy (TEM) and small angle X-ray diffraction (XRD) confirmed that the imprinted mesoporous organosilica shell preserved a highly ordered 2D mesostructure. The Brunauer–Emmett–Teller (BET) analysis found the surface area was 946 m 2 g −1 . The saturated adsorption capacity of MIIMS toward cadmium reached up to 25.2 mg g −1 (0.224 mmol g −1 ) at pH 5.0. The adsorption of cadmium reached an equilibrium within 4.5 min. The results of a selectivity study revealed that the adsorption capacity for Cd 2+ is much high than other co-existing heavy metal ions. The adsorption efficiency of MIIMS was above 94.2% after six extraction-stripping cycles. The MIIMS can efficiently remove cadmium ions in water treatment applications.